(3GOGQI GdeNGRf (B/s - (3GdYdGb, HTjQ YHGSs; (3GdUjQaj, eMeO YHO GdaJGM s ((3YeGf(B: s (3OGQ GdefGgL ddfTQ h GdJhRjY(B, s, 2006)
(3GdeSGMI GdJNRjfjI h GOGQI GdehGQO h cPG ehbY GdeNRf h GfhGY GdeSJhOYGJ h JcfhdhLjG GdeYdheGJ aj eLGd GdJNRjf h CNjQG JWHjbGJ YGeI(B.s
(3eQGLY U(B.206s
Keywords: (3GOGQI GdeNGRfs; (3GOGQI GdeSJhOYGJs; (3GdeNGRfs